PHILOSOPHY OF CULTURE YU. M. LOTMAN: COGNITIVE DIALOGUE SEMIOTICS AND HISTORICAL ANTHROPOLOGY PURPOSE - S. SH. Aytov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of this work is to study the cognitive interferences philosophical and social sciences and humanities. The aim of the article is to analyze the cognitive interaction of historical anthropology and semiotics in the space of philosophical-cultural concepts Lotman. Methodology. The methodology of this work includes the theoretical approaches, such as system-structural method, interdisciplinary method, comparative and source study methods. Teoretical basis and results. Philosophy of Culture Lotman contains a large number of cognitive dimensions. Significant role in the cognitive universe of his work is semiotics and historical anthropology. However interaction of these semiotic components of Lotman creation little explored yet. The latter applies to the redesign of the historical-anthropological ideas and research scientist. Conclusions. Understanding the interaction of cognitive semiotics and historical anthropology in the space of culture philosophy of Lotman logically leads to the conclusion that the effectiveness of cognitive symbiosis methodological approaches these sciences. In particular, the cognitive structure allows us to study the underlying causes of the motives and actions of individuals and entire societies past. The realization of semiotic, historical and anthropological methods allows us to analyze the underlying mechanisms of the spiritual culture and social and cultural institutions of societies from different historical periods.